New Ursane Glycoside from the Roots of Asparagus racemosus - A. Siddiqui, Nasir; Ali, Mohd; Ahmad, Ateeque; H. Khan, Tajdar; Ahmad, Aftab (Asian Journal of Chemistry, 2013)
One new compound urs-1,12,19-trien-3b-ol-28-oic acid-3b-D-glucopyranosyl (4'-1'')-b-D-glucopyranoside (1) along with five known compounds (2-6) have been isolated from the roots of Asparagus racemosus. Their structures have been elucidated with the help of 500/125 MHz NMR using 1D and 2D spectral methods viz: 1H and 13C NMR, ESIMS and aided by IR spectroscopy.